2008
DOI: 10.1111/j.1651-2227.2008.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety in paediatric clinical trials – a 7‐year review

Abstract: About 11% of trials have a moderate or severe ADR. All paediatric clinical trials should have a SMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 28 publications
2
50
2
Order By: Relevance
“…There is widespread concern that most medicines used in the field of paediatrics are unlicensed or off-label. 2,86 It has been suggested that the pharmaceutical industry has been reluctant to conduct clinical trials of medicines because of the small market for the sale of drugs for babies and children, making investment in expensive research less attractive. Other reasons may include concerns about the ethics of conducting research in children, difficulties with blood sampling and recruiting sufficient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…There is widespread concern that most medicines used in the field of paediatrics are unlicensed or off-label. 2,86 It has been suggested that the pharmaceutical industry has been reluctant to conduct clinical trials of medicines because of the small market for the sale of drugs for babies and children, making investment in expensive research less attractive. Other reasons may include concerns about the ethics of conducting research in children, difficulties with blood sampling and recruiting sufficient numbers.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Sammons and colleagues evaluated the drug toxicity studying 739 pediatric clinical trials published over 7 years [6]. Seventy one percent of …”
Section: Risks Of Clinical Trials In Neonatesmentioning
confidence: 99%
“…There are additional ethical challenges because children lack the capacity to understand the risks involved in trials and depend upon adults to make decisions for them [110]. In a review of 739 paediatric trials from 1996 to 2002, 523 (71%) reported adverse drug reactions, but only 13 (2%) of the trials had safety monitoring committees [4]. Since then, trial governance is becoming more stringent with a requirement for an independent safety monitoring board with paediatric expertise, who can appreciate the uniqueness and unpredictability of responses in children [76,111].…”
Section: Ethics Of Paediatric Clinical Trialsmentioning
confidence: 99%
“…Since the acknowledgement of children as 'therapeutic or pharmaceutical orphans' in the 1960s [1][2][3] there has been a worldwide recognition of the need to conduct trials of medicines used in children as a mechanism to improve the health of children [4][5][6][7]. Significant advances in child health have resulted from the conduct of paediatric trials.…”
Section: Imperative To Conduct Trials In Childrenmentioning
confidence: 99%
See 1 more Smart Citation